Molecular Epidemiology of Tinea Pedis Among Palm Oil Plantation Workers in Labuhan Batu Utara Regency, Indonesia: Identification of Causative Fungal Pathogens - Haryani, Sela; Riri Arisanty Syafrin Lubis; Rinna Azrida (Phlox Institute: Indonesian Medical Research Organization, 2023)
Introduction: Tinea pedis, commonly known as athlete's foot, is a prevalent fungal infection affecting the feet. Palm oil plantation workers, often exposed to humid and warm conditions, are at an increased risk of contracting this condition. This study aimed to investigate the molecular epidemiology of tinea pedis among palm oil plantation workers in Labuhan Batu Utara Regency, Indonesia, and identify the causative fungal pathogens. Methods: A cross-sectional study was conducted among palm oil plantation workers in Labuhan Batu Utara Regency. Demographic data and clinical information were collected through questionnaires. Skin scrapings were obtained from the affected areas of the feet and subjected to microscopic examination and fungal culture. Molecular identification of the isolated fungi was performed using DNA sequencing of the internal transcribed spacer (ITS) region. Results: A total of 250 palm oil plantation workers participated in the study. The prevalence of tinea pedis was found to be 42.8%. The most common clinical presentations were interdigital scaling and maceration (65.2%), followed by vesicular lesions (23.1%) and hyperkeratosis (11.7%). The predominant fungal pathogens identified were Trichophyton rubrum (58.3%), Trichophyton mentagrophytes (27.8%), and Epidermophyton floccosum (13.9%). Conclusion: Tinea pedis is a significant health problem among palm oil plantation workers in Labuhan Batu Utara Regency. The identification of the causative fungal pathogens is crucial for implementing effective preventive and therapeutic measures to control the spread of this infection.